(3YLGdI GdeHJOj haVGdI GdoefJgis - (3CHh HcQ Rjf GdOjf eMeO Hf ehSi Hf YKeGf Hf MGRe GdMGRej, GdMGRej,J (B584 (3g` s
(3ChdgG (B:s
(3CeG HYO , aGYde habfG Gddg hEjGc Cf GdWGdH ddMOjK jaJbQ Edi eYQaI Yde GdMOjK EP gh BdJg , hHg jecf JUMjMg hJKHJg s
(3BNQgG (B:s
(3hgPG HGH hGSY def JHYg hQGe dGWdGY Ydi ZhGeVg hCSGdjH GdGNJdGa ajg GbJUQJ Ydi GdbOQ GdPi CedjJg s
(3GfXQ GjVG Qbe (B330 (3JGQjNs
(3QJHg JQJjHG gLGFkjs
(3hHChd GdfSNI SeGYGJ JfJgj Edi GdeDda SfI (B583 (3g`s
(3fSNI KGfjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B117s
Keywords: (3GdJGQjNs